2014
DOI: 10.1155/2014/231090
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Imaging in Radiation Therapy Planning: Past, Present, and Future

Abstract: The use of ionizing radiation for cancer treatment has undergone extraordinary development during the past hundred years. The advancement of medical imaging has been critical in helping to achieve this change. The invention of computed tomography (CT) was pivotal in the development of treatment planning. Despite some disadvantages, CT remains the only three-dimensional imaging modality used for dose calculation. Newer image modalities, such as magnetic resonance (MR) imaging and positron emission tomography (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
106
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(114 citation statements)
references
References 39 publications
0
106
0
2
Order By: Relevance
“…The accuracy of radiation therapy depends on the conformal deposition of ionizing radiation to the target volume and the efforts to spare its neighboring healthy tissues 4, 5. To achieve high‐precision treatments, imaging plays a crucial role in planning and delivering radiation beams 6, 7. It has been demonstrated that the use of image‐guided radiation therapy (IGRT) may improve the clinical outcome of patients undergoing radiation therapy 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of radiation therapy depends on the conformal deposition of ionizing radiation to the target volume and the efforts to spare its neighboring healthy tissues 4, 5. To achieve high‐precision treatments, imaging plays a crucial role in planning and delivering radiation beams 6, 7. It has been demonstrated that the use of image‐guided radiation therapy (IGRT) may improve the clinical outcome of patients undergoing radiation therapy 8, 9.…”
Section: Introductionmentioning
confidence: 99%
“…Currently used single modal imaging techniques like magnetic resonance imaging (MRI), computed tomography (CT), positron emission tomography (PET), and optical imaging are not sufficient in many cases for conclusive diagnosis of metastatic or circulating cancer cells in biological tissues. These noninvasive imaging technologies have low tissue contrast, low or moderate sensitivity, low spatial resolution, and low specificity . However, with the rapid advance in nanotechnology, it has become possible to engineer multimodal nanoprobes that integrate nanoparticles with multicomponent nature into a single nano system.…”
Section: Biological Applications Of Ucnpsmentioning
confidence: 99%
“…On the right hand side, images of seven representative lesions are shown. It is worth noting that for volumes around 10 cm 3 , it is difficult to differentiate the intratumor heterogeneity levels, which is more evident at volume levels around 30-35 cm 3 . The contours shown in green correspond to the segmentation of the functional volumes using the Flab algorithm.…”
Section: Valeur Clinique Des Nouveaux Indices : Limites Actuelles Et mentioning
confidence: 99%
“…Son rôle est maintenant de plus en plus important dans le cadre du suivi et de l'évaluation de la réponse thérapeutique [2] ainsi que de la radiothérapie, notamment pour la planification et la définition des cibles [3]. La combinaison des deux modalités permet, d'une part, une correction d'atténuation précise des données TEP en exploitant les informations sur la densité dans chaque voxel fournies par la TDM.…”
Section: Introductionunclassified